Comparative Outcomes of Laparoscopic Versus Open Appendectomy in Children Aged 9–13 Years: A Retrospective Study: Hasil Perbandingan antara Laparoskopi dan Bedah Terbuka pada Pengangkatan Appendiks pada Anak Usia 9–13 Tahun: Studi Retrospektif - Sarmad Jaafar Mohammed Alrubaye (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Acute appendicitis is one of the most common causes of emergency abdominal surgery in children and appendectomy remains the standard treatment. Specific Background: While open appendectomy has long been the traditional surgical approach, laparoscopic appendectomy has gained attention in pediatric surgery because of its minimally invasive characteristics and potential benefits for postoperative recovery. Knowledge Gap: Despite numerous comparisons in adult populations, focused evidence evaluating surgical outcomes among school-aged children in specific clinical settings remains limited. Aims: This study compares the clinical and functional outcomes of laparoscopic and open appendectomy in children aged 9–13 years, particularly regarding operative time, postoperative recovery, hospital stay, complications, and return to daily activities. Results: A retrospective analysis of 100 pediatric patients treated between August 2023 and August 2025 showed that laparoscopic appendectomy was associated with reduced postoperative analgesic requirements, earlier oral intake, shorter hospital stay, and faster return to normal activities. Although operative time was slightly longer in the laparoscopic group, overall complication rates were lower and major complications were not significantly different between the groups. Novelty: This study provides focused clinical evidence on surgical outcomes specifically in children aged 9–13 years within a comparative framework. Implications: The findings support the consideration of laparoscopic appendectomy as a preferred surgical option in pediatric appendicitis when appropriate expertise and resources are available. Keywords: Pediatric Appendicitis, Laparoscopic Appendectomy, Open Appendectomy, Postoperative Recovery, Pediatric Surgery Key Findings Highlights Laparoscopic surgery demonstrated reduced postoperative pain and shorter hospitalization. Children undergoing minimally invasive procedures resumed normal activities sooner. Surgical complications were lower overall despite slightly longer operative duration.